A postresection perfusion deficit in the right colon is an independent predictor of perioperative outcome after major hepatectomy - Birgin, Emrullah; Yang, Cui; Brunner, Anna; Hetjens, Svetlana; Rahbari, Mohammad; Bork, Ulrich; Reißfelder, Christoph; Weitz, Jürgen; Rahbari, Nuh Nabi (Journal of hepato-biliary pancreatic sciences, 2022)
The impact of hepatectomy on splanchnic perfusion has been poorly documented. In this study Birgin and colleagues revealed that major hepatectomy induces a significant reduction in splanchnic perfusion in the splanchnic system.